2015
DOI: 10.1039/c5sc02923f
|View full text |Cite
|
Sign up to set email alerts
|

Selective photocatalytic C–C bond cleavage under ambient conditions with earth abundant vanadium complexes

Abstract: Chemoselective aliphatic carbon–carbon bond activation photocatalyzed by vanadium oxo complexes under ambient conditions and visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
140
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(143 citation statements)
references
References 51 publications
(137 reference statements)
3
140
0
Order By: Relevance
“…[47] The direct CÀCb ond cleavage was confirmed by 13 Ca nd 2 Hi sotope-labeling experiments, during which no scrambling of the benzylic hydrogen atom before or after bond cleavage was observed. [47] The direct CÀCb ond cleavage was confirmed by 13 Ca nd 2 Hi sotope-labeling experiments, during which no scrambling of the benzylic hydrogen atom before or after bond cleavage was observed.…”
Section: V Complexesmentioning
confidence: 84%
See 1 more Smart Citation
“…[47] The direct CÀCb ond cleavage was confirmed by 13 Ca nd 2 Hi sotope-labeling experiments, during which no scrambling of the benzylic hydrogen atom before or after bond cleavage was observed. [47] The direct CÀCb ond cleavage was confirmed by 13 Ca nd 2 Hi sotope-labeling experiments, during which no scrambling of the benzylic hydrogen atom before or after bond cleavage was observed.…”
Section: V Complexesmentioning
confidence: 84%
“…The Soo group reported aV V -based photocatalyst that cleaved CÀCb onds in aliphatic alcohols with high regioselectivity under visible-light irradiationa nd ambient conditions to generate two valuable products, aryl aldehydes and formate, in moderate to high yields (Scheme 9). [47] The direct CÀCb ond cleavage was confirmed by 13 Ca nd 2 Hi sotope-labeling experiments, during which no scrambling of the benzylic hydrogen atom before or after bond cleavage was observed. The mechanism wasp robed by time-dependent (TD)DFT calculation, which suggested that excitation of the ligand-to-metal chargetransfer (LMCT)band in the alcohol-V V -photocatalyst complex induced hemolytic CÀCb ond cleavage.…”
Section: V Complexesmentioning
confidence: 84%
“…A 1,4‐hydroquinone/copper nanoparticle catalytic system was used for C α C β bond oxidative cleavage under visible‐light irradiation with low yields of aromatic aldehydes and phenols . Soo and co‐workers reported a more efficient vanadium photocatalyst . The vanadium complex harvested visible light and realized C α C β bond oxidative cleavage.…”
Section: The Challengesmentioning
confidence: 99%
“…[57,58] While compounds with aromatic substituents show lifetimes below 200 ns with quantum yields < 1%,c omplexes with bulky alkyl substituents (R = adamantyl, tert-butyl) exhibit longer-lived emission with lifetimes and quantum yields of up to 15.1 msa nd 20 %, respectively.M ore recently,h ydrazone-imidate vanadium(V) oxo complexes with luminescence lifetimes of up to 9.9 ns in acetonitrile have been utilized in photocatalysis. [59,60] The exciteds tate was assigned as LMCT (O 2À !V V )v ia density functional theory.…”
Section: Introductionmentioning
confidence: 99%